Improved mechanical and wear characteristics of hypereutectic aluminium-Silicon alloy matrix composites and empirical modelling of the wear response. Issue 1 (1st January 2020) - Omodara, O; Daramola, OO; Olajide, JL; Adediran, AA; Akintayo, OS; Adewuyi, BO; Desai, DA; Sadiku, ER
Abstract: For the first time, Silicon Carbide-Zinc Oxide-Graphite reinforced hypereutectic Aluminium–Silicon composites were fabricated by two-step stir casting. The mechanical properties and abrasive wear performance of the composites were experimentally tested. A multilevel factorial design of experiment was conducted to develop a numerical model for predicting the wear rate of composites and optimization of their wear performance as a function of reinforcement characteristics. The results indicated that high content of silicon carbide in the composites superlatively enhanced hardness, tensile strength and fracture toughness by 69.04%, 163.22% and 77.42%, respectively. Correspondingly, high content of graphite indicated superlative wear resistance of 95.87% reduction in wear index while high zinc oxide content revealed enhanced fracture toughness highly comparable with that observed for high silicon carbide content. Nevertheless, in comparison with the monolithic alloy, the trade-offs in the strains-to-fracture of the composites were more pronounced with high silicon carbide content. The developed 2-factor-interaction effects model strongly agrees with the experimental results after passing various model validity tests available in Design Expert Software. It revealed that the composition of reinforcing constituents influenced the model more than the volume fraction, and the interaction between the composition of reinforcement constituents and volume fraction.